Narrativas Testimoniales de Mujeres en el Posconflicto Colombiano: Un Enfoque Pedagógico para la Reconstrucción de la Memoria Histórica - Velásquez, Sandra Lorena (Universidad Antonio Nariño, 2023)
This compilation monograph analyzes the narratives and testimonies of women who have directly or indirectly experienced violence and suffering during the armed conflict. These stories reveal the diverse ways in which women have been affected, but also highlight their resilience and capacity for transformation. Through their testimonies, the individual and collective experiences of the women are made visible, and the gender dynamics and challenges they have faced in the post-conflict context are analyzed.